Transient Studies of Ghana Research Reactor-1 after Nineteen (19) Years of Operation Using PARET/ANL Code - Mweetwa, Bright M.; Amoako, Emmanuel A.; Akaho, Edward H. K. (Scientific research, 2017)
The Program for the Analysis of Reactor Transients/Argonne National Laboratory (PARET/ANL) code was used to predict the thermal hydraulic behaviour of the Ghana Research Reactor-1 after adding 9.0 mm of beryllium to the top shim tray of the core. The core was analysed for reactivity insertions 2.1 mk, 3.0 mk, 4.0 mk, 5.0 mk and 6.7 mk, respectively. The reactor is still safe to operate in the range 2.1 mk to 4.0 mk. However, 2.1 mk would be ideal since the reactor automatic shutdown (SCRAM) is set not to exceed 120% of reactor nominal power
Keywords: Reactivity Insertion; Transients.; Control Rod Worth; Power Peaking Factor; Moderator Reactivity Coefficient; Neutronic Parameters